A C57BL/6J Fancg-KO Mouse Model Generated by CRISPR/Cas9 Partially Captures the Human Phenotype - Shah, Ronak; van den Berk, Paul C. M.; Pritchard, Colin E. J.; Song, Ji-Ying; Kreft, Maaike; Pilzecker, Bas; Jacobs, Heinz (International journal of molecular sciences, 2023)
Fanconi anemia (FA) develops due to a mutation in one of the FANC genes that are involved in the repair of interstrand crosslinks (ICLs). FANCG, a member of the FA core complex, is essential for ICL repair. Previous FANCG-deficient mouse models were generated with drug-based selection cassettes in mixed mice backgrounds, leading to a disparity in the interpretation of genotype-related phenotype. We created a Fancg-KO (KO) mouse model using CRISPR/Cas9 to exclude these confounders. The entire Fancg locus was targeted and maintained on the immunological well-characterized C57BL/6J background. The intercrossing of heterozygous mice resulted in sub-Mendelian numbers of homozygous mice, suggesting the loss of FANCG can be embryonically lethal. KO mice displayed infertility and hypogonadism, but no other developmental problems. Bone marrow analysis revealed a defect in various hematopoietic stem and progenitor subsets with a bias towards myelopoiesis. Cell lines derived from Fancg-KO mice were hypersensitive to the crosslinking agents cisplatin and Mitomycin C, and Fancg-KO mouse embryonic fibroblasts (MEFs) displayed increased γ-H2AX upon cisplatin treatment. The reconstitution of these MEFs with Fancg cDNA corrected for the ICL hypersensitivity. This project provides a new, genetically, and immunologically well-defined Fancg-KO mouse model for further in vivo and in vitro studies on FANCG and ICL repair.